Bonding Strength of Beech Plywood Glued with Alcohol-Soluble Phenol-Formaldehyde Resin - Miglena Valyova; Daniel Koynov (Drvna Industrija)
The present study examines the bonding strength of five-layer plywood made from beech wood (Fagus sylvatica L.). An alcohol-soluble phenol-formaldehyde (PF) resin as an adhesive between the veneer sheets was used. Various pressing factors, showing the effect of the varying ratio between them, were applied. The experimental samples both in a dry state and after immersion in boiling water for one hour were tested. The results clearly demonstrated that the bonding strength is very high when using the alcohol-soluble PF resin and meets the requirements of the standard BDS EN 314-2: 2002. The best bonding strength values were obtained at a presstemperature of 145 °C, adhesive spread of 150 to 170 g/m2, and initial adhesive temperature of 30-40 °C.